1993
DOI: 10.1021/bi00064a031
|View full text |Cite
|
Sign up to set email alerts
|

Purification and further characterization of macrophage 70-kDa protein, a calcium-regulated, actin-binding protein identical to L-plastin

Abstract: We have previously identified a macrophage 70-kDa, actin-bundling protein as a constituent of actin-based cytoplasmic gel and showed that its association with or dissociation from cytoplasmic gels was remarkably affected by submicromolar calcium. In this study, we purified the 70-kDa protein from soluble cytosolic extracts and carried out a more detailed characterization. The amino acid sequences of four peptidic fragments, obtained from the purified protein by enzymatic or chemical cleavage, were completely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 41 publications
4
36
0
Order By: Relevance
“…5B). Conversely, F-actin binding of the closely related L-plastin isoform was Ca 2+ sensitive when analysed under identical experimental conditions (data not shown), as observed previously (Namba et al, 1992;Pacaud and Derancourt, 1993). This result confirmed the observation that plastins differ in their Ca 2+ regulation, as previously proposed (de Arruda et al, 1990;Lin et al, 1994).…”
Section: ±1×10supporting
confidence: 90%
See 1 more Smart Citation
“…5B). Conversely, F-actin binding of the closely related L-plastin isoform was Ca 2+ sensitive when analysed under identical experimental conditions (data not shown), as observed previously (Namba et al, 1992;Pacaud and Derancourt, 1993). This result confirmed the observation that plastins differ in their Ca 2+ regulation, as previously proposed (de Arruda et al, 1990;Lin et al, 1994).…”
Section: ±1×10supporting
confidence: 90%
“…These results confirmed the F-actinstabilizing capacity of T-plastin and ABD1. It is documented that physiological Ca 2+ concentrations (1-2 µM) inhibit the F-actin binding of L-plastin (Namba et al, 1992;Pacaud and Derancourt, 1993), raising the possibility that the stabilizing effects we observed with T-plastin were also Ca 2+ -dependent. Because cell extracts contain other Ca 2+ -regulated proteins like gelsolin that might also contribute to actin turnover in comets (Samarin et al, 2003), we decided to examine the effect of Ca 2+ in the F-actin depolymerization assay (Fig.…”
Section: ±1×10mentioning
confidence: 80%
“…Our data suggest that L-plastin is likely cleaved proteolytically so that the N-terminal EF-hand domain is removed in response to enoxacin. The EF-hand binds calcium and mediates inhibition of binding of L-plastin to microfilaments in the presence of calcium (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Human tissues were (lanes) colon adenocarcinoma cell line Caco-2 (1), colonic tumor (2) and normal colon (3) from one patient, and small intestine (4) and colon (5) from another patient. Rat tissues were (lanes) jejunal epithelium (6), colon (7), ileum (8), jejunum (9), duodenum (10), uterus (11), kidney (12), spleen (13), leg muscle (14), liver (15), stomach (16), lung (17), heart (18), esophagus (19), and brain (20 demonstrated that calcium inhibits actin bundling (23)(24)(25). In the homologous region of yeast Sac6p, critical positions are occupied by residues that would prevent calcium binding, suggesting that this protein is not calcium regulated in Saccharomyces cerevisiae (1).…”
Section: Y E L Q D L F K E a S L P L P G Y K V R E I V E K I L S V mentioning
confidence: 99%